Psychological consequences and differential impact of the COVID-19 pandemic in patients with mental disorders. (August 2021) - Favreau, Matthias; Hillert, Andreas; Osen, Bernhard; Gärtner, Thomas; Hunatschek, Sandra; Riese, Moritz; Hewera, Karina; Voderholzer, Ulrich
Highlights: Patients with mental disorders seem to be differentially affected by the pandemic. Differences in psychological consequences between diagnostic groups remain unclear. Treatment impairment or increased need of therapeutic support was frequently stated. Highest rates of symptom deterioration were observed in AN and depressive disorders. Results indicated a high psychosocial impairment due to the pandemic. Abstract: Objective: People with mental disorders might be differentially affected by the COVID-19 pandemic. The aim of the current study was to evaluate the impact of the pandemic on patients with various psychiatric disorders who were admitted to inpatient treatment. Methods: Five-hundred thirty-eight inpatients with mental disorders participated in a survey about psychological consequences of the pandemic between March-December 2020. We examined the perceived burden by restrictions and worries, changes in health care utilization, and helpfulness of coping strategies. Results: More than 50% reported any worsening of symptoms, 40% stated increased need of therapeutic support. High rates of symptom deterioration were observed for depressive symptoms (>55%), anxiety (>40%), and sleeping behavior (>40%). Treatment impairment was stated by 27.9%. Patients with anxiety disorders were less affected by contact restrictions compared with eating disorders and depression. Patients with anorexia nervosa and post-traumatic stress disorder experienced higher helpfulness by daily structuring than patients with depression. Discussion: About half of our sample of psychiatric patients experienced symptom deterioration due to the pandemic and about one quarter reported impairment of treatment modalities. Especially patients with eating disorders and depressive disorders were more frequently affected. The results indicate a needed improvement of treatment options during a pandemic.